El petróleo y el gas como instrumentos de política exterior: el caso de Rusia - Castro, Julissa (2014)
Just as oil constituted an important factor in the collapse of the USSR, today the energy resources Russia counts with are the political-economic weapons on which this country seeks to reposition in the international arena. Russia not only promotes the end of the unipolar world, but also intends to become a major power in the twenty first century. In order to achieve this, Kremlin has as a goal the reestablishment of its influence in the post-soviet space and ensure their relative power as a main supplier of gas against the Europe Union. To do this, they are using energy cooperation agreements with clear political overtones, even a more aggres- sive diplomacy, such as oil or gas cuts to countries that deviate from their sphere of political interest.